Gambaran Kepatuhan Penggunaan Obat Antituberkulosis pada Pasien Tuberkulosis Paru di Puskesmas Pahandut Kota Palangkaraya - Anna Singgih D.P. Priyaputranti; Fita Rahmawati; Nanang Munif Yasin (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Tuberculosis is a communicable disease caused by Mycobacterium tuberculosis. Indonesia's health profile stated that the number of tuberculosis cases in 2021 was 397,377 cases, indicating an increase compared to 2020 of 351,936 cases. Medication adherence is crucial for the management of tuberculosis. Some failures of tuberculosis treatment are caused by non-adherence. Detection of medication adherence is important to help control tuberculosis. This study aimed to describe the medication adherence of antituberculosis drugs and the predictive factor among pulmonary tuberculosis of drug-susceptible tuberculosis. This study uses a cross-sectional design with retrospective data collection. Drug therapy monitoring and TB-01 form collected non-adherence identification from January to February 2023 at Puskesmas Pahandut, Palangkaraya city, which involved 35 patients. The predictive factor was identified by an interview with the patient, the treatment observers, and the chief tuberculosis programmer. Adherence was measured by medication left over at the visit. The results showed 24 (77%) adherent patients and 8 (23%) non-adherent patients. The predictive factor involved seven dimensions patient-centered (lack of motivation, forgetting to take medicine, unacknowledged information by public health care provider, confusion about how to take medicine), access factors, social and lack of role of the treatment observers. The improvement role of healthcare providers in public health centers and treatment observers is prominent in increasing patient adherence.